Examining the use of head impact sensors in school sports (Mathematica Policy Research, 2017)
To help researchers and policymakers identify the best ways to prevent concussions among young athletes, Mathematica conducted a pilot project to explore the experiences at two high schools that outfitted athletes with head impact sensors. Head impact sensors are used to measure the g forces athletes sustain during contact in sport. Although these sensors cannot determine whether or not the athlete sustained a concussion, they serve as a promising tool for research.